Islamic Values in the Context of English Learning and Teaching - Zaitun Zaitun; Siska Kusuma Wardani (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2018)
The aim of this research is to describe the Islamic values in the process of teaching English. This research was conducted at SD Labschool FIP UMJ for about 3 months starting from June 2018 until August 2018. This study focuses on English teaching and learning process at 4th graders. The study applied a qualitative descriptive research method which used observation and documents as the instruments in collecting the data. The writers observed both the school and 4th grade class and used the syllabus, lesson plan and English textbook as the documents. The analysis of the data showed that the Islamic values had been being well-built in the area of the school together with the school activities. While in the class observation the writer found that the Islamic values were not being applied yet in the process of teaching and learning English, besides, it was also found that syllabus, lesson plan, and textbook did not insert any Islamic values at all either in the content of the materials or in the teaching and learning activities. Thus this research study concludes that the Islamic values did not fully exist yet in the process of teaching English to the 4th graders of SD Labschool FIP UMJ.